Analisis Dampak Game Online terhadap Remaja: Kajian Studi Literatur - Fahmi Kurniawan; Luthfan Jiwa Pangestu; Sri Mulyeni (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
The rapid and significant development of technology in the world has made online games a very popular form of entertainment among teenagers and students. Easy access to online games through gadgets has led to an increase in the number of teenagers playing online games. This condition has both positive and negative impacts on education, particularly on students' interest in learning. This study aims to analyze in depth the influence of online games on the lives and learning achievements of teenagers based on previous articles. We chose a literature study method for this research, and the data sources were obtained from articles relevant to the discussion. The data collection technique was carried out by reading and examining important information from the articles used. The results of the study show that online games have both positive and negative impacts on teenagers. The positive impacts can be seen in games that are educational and relevant to learning, as they can increase motivation, curiosity, and skills in teenagers. However, if played excessively and without supervision, online games tend to reduce concentration, decrease study time, and impact academic achievement, psychological well-being, and the health of adolescents. Therefore, the role of parents and teachers is crucial in controlling, guiding, and monitoring the use of online games so that adolescents can use them wisely and support the learning process wherever they are.